Appendix C : quality performance indicators : from Double degrees : research pathways, enabling cross disciplinarity and enhancing international competitiveness. - Moulton, Bruce; Iyer, R. Mahalinga; Shortis, Mark; Vuthaluru, Hari B.; Xing, Ke (Australian Learning and Teaching Council (ALTC), 2011)
The existing structures of the studied dual degrees enable students to complete two degrees, which would separately take seven years to complete, in five to five and a half years. This is an appendix from the final report of a project that examined the documented rationale for the shortening of the dual degree offering. It focuses on quality performance indicators at selected Australian universities.